2018
DOI: 10.1080/15476286.2018.1536593
|View full text |Cite
|
Sign up to set email alerts
|

A potential role of extended simple sequence repeats in competing endogenous RNA crosstalk

Abstract: MicroRNA (miRNA)-mediated crosstalk between coding and non-coding RNAs of various types is known as the competing endogenous RNA (ceRNA) concept. Here, we propose that there is a specific variant of the ceRNA language that takes advantage of simple sequence repeat (SSR) wording. We applied bioinformatics tools to identify human transcripts that may be regarded as repeat-associated ceRNAs (raceRNAs). Multiple protein-coding transcripts, transcribed pseudogenes, long non-coding RNAs (lncRNAs) and circular RNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Compelling evidence suggests that lncRNAs can function as a sponge of miRNAs, leading to derepression of miRNA target genes. 24 , 25 With the consideration that LINC-PINT and miR-767-5p exert opposite effects on thyroid cancer progression, we hypothesized that LINC-PINT may sponge miR-767-5p to induce the expression of TET2. In line with this hypothesis, we found that LINC-PINT overexpression leads to an increase in TET2 protein levels, which is reversed by miR-767-5p coexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that lncRNAs can function as a sponge of miRNAs, leading to derepression of miRNA target genes. 24 , 25 With the consideration that LINC-PINT and miR-767-5p exert opposite effects on thyroid cancer progression, we hypothesized that LINC-PINT may sponge miR-767-5p to induce the expression of TET2. In line with this hypothesis, we found that LINC-PINT overexpression leads to an increase in TET2 protein levels, which is reversed by miR-767-5p coexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that lncRNAs competitively bind with miRNAs to regulate target genes expression (28). Online forecasting software predicted that miR-216a-5p might be a target of ZEB1-AS1.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of their wide distribution and high mutation rate in eukaryotic genomes [ 1 ], SSRs have been used in genetic diversity and population structure studies [ 2 , 3 , 4 , 5 ], for discrimination among species or breeds [ 6 , 7 ], in marker-assisted selection [ 8 , 9 , 10 ] and in evolution analysis [ 11 ]. In humans, SSRs were predicted to be bound by protein-coding transcripts, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) and affect competing endogenous RNA crosstalk [ 12 ]. Besides being an important category of regulatory elements, polymorphic SSRs could quantitatively regulate the transcription of tissue-specific genes in the development of the frog embryo [ 13 ].…”
Section: Introductionmentioning
confidence: 99%